Exclusive Endoscopic Laser-Stapedotomy: Feasibility of an Ovine Training Model. Issue 7 (August 2021) - Beckmann, Sven; Yacoub, Abraam; Fernandez, Ignacio Javier; Niederhauser, Laura; Fermi, Matteo; Caversaccio, Marco; Bonali, Marco; Anschuetz, Lukas
Abstract : Objective: Stapedotomy is an effective treatment for conductive hearing loss associated with otosclerosis. However, the procedure, especially using the endoscopic technique requires extensive training and experience for optimal results. Due to limited training options in endoscopic stapes surgery, we aim to develop an ovine stapedotomy model and assess its feasibility for surgeons at different training levels. Methods: A fully endoscopic ovine laser-stapedotomy model was developed and described. During repetitive dissections, surgical time required for the different steps to assess the training curve and associated intraoperative complications were recorded in three surgeons of different training level. Additionally, subjective feedback was assessed. Results: Successful endoscopic laser-stapedotomy was performed in 25 cases in the ovine model. Assessment of surgical time revealed a stable curve for the experienced surgeon (mean 15:01 min) for the whole training with no intraoperative complications. The fellow showed a gradual reduction of surgical time from 27:21 (first five cases) to 24:10 minutes (last five cases) and the resident a reduction from 42:38 to 21:08 minutes respectively. The assessed learning curve for the trainees revealed a significant association between the operative time and observed intraoperative complications. Discussion: In this study, an ex-vivo model for exclusively endoscopic laser-stapedotomy was developed and tested for feasibility. We suggest the ovine model as a cost-effective, easily available, and realistic training model for future otologic surgeons. The surgeons were able to improve their performance with satisfactory results despite the small number of cases. Abstract : Supplemental Digital Content is available in the text